2021
DOI: 10.22541/au.161555584.41724264/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide evolutionary signatures of climate adaptation in spotted sea bass inhabiting different latitudinal regions

Abstract: Temperature is an important climatic factor that shapes the distribution of eurythermal species. Thermal adaptation of species is important to both evolutionary biology and climate-change biology because it frequently leads to latitudinal gradients of various phenotypes among populations. Spotted sea bass (Lateolabrax maculatus) has a broad latitudinal distribution range along the marginal seas of the Northwest Pacific, providing an excellent teleost model for climate adaptation studies. We generated over 8.57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Variability in water temperature is known to drive divergence in marine species by selecting thermal tolerance at multiple life history stages, affecting traits related to growth, reproduction and movement(Johansen & Jones, 2011;Pankhurst & Munday, 2011;Rountrey et al, 2014). Indeed, other studies have demonstrated that temperature is a significant determinant of adaptive divergence and genetic structure in marine species, such as Parastichopus californicus exhibiting different bottom temperatures in the coastal region of British Columbia and southeastern Alaska(Xuereb et al, 2018), and Sillago japonica(Han et al, 2021) and Lateolabrax maculatus (;Chen et al, 2021) inhabiting spatially varying temperature regimes in the Northwest Pacific Ocean. Even though temperature sometimes may not be the direct causation of selection, other factors closely associated with temperature could directly contribute to adaptation.For example, rising water temperatures could reduce the overall aerobic scopes of aquatic ectotherms and smaller aerobic scopes imply that less energy remains for supporting physiological performance and fitness-related activities(Pörtner & Knust, 2007).Overall, the obvious heterogeneity in environmental factors might have resulted in the divergent selection of specific genes,…”
mentioning
confidence: 99%
“…Variability in water temperature is known to drive divergence in marine species by selecting thermal tolerance at multiple life history stages, affecting traits related to growth, reproduction and movement(Johansen & Jones, 2011;Pankhurst & Munday, 2011;Rountrey et al, 2014). Indeed, other studies have demonstrated that temperature is a significant determinant of adaptive divergence and genetic structure in marine species, such as Parastichopus californicus exhibiting different bottom temperatures in the coastal region of British Columbia and southeastern Alaska(Xuereb et al, 2018), and Sillago japonica(Han et al, 2021) and Lateolabrax maculatus (;Chen et al, 2021) inhabiting spatially varying temperature regimes in the Northwest Pacific Ocean. Even though temperature sometimes may not be the direct causation of selection, other factors closely associated with temperature could directly contribute to adaptation.For example, rising water temperatures could reduce the overall aerobic scopes of aquatic ectotherms and smaller aerobic scopes imply that less energy remains for supporting physiological performance and fitness-related activities(Pörtner & Knust, 2007).Overall, the obvious heterogeneity in environmental factors might have resulted in the divergent selection of specific genes,…”
mentioning
confidence: 99%